Bali Bebas Sampah Plastik (menuju “Clean and Green Island”) - Ekapria Dharana Kubontubuh (Bali Membangun Bali: Jurnal Bappeda Litbang, 2019)
Waste becomes an environmental problem in Bali and requires attention immediately. Plastic waste is the second largest component in waste generation in Bali, which very harmful to health and threatens Bali tourism. Plastic waste production in Bali reaches 268 tons every day and only 29.4% of plastic waste is disposed of to landfills. While 44.5% of plastic waste is not processed so that pollutes the environment especially the river and the sea. The Bali Provincial Government realize the dangers of plastic waste and tried to limit generations by issuing regulations that limit the generation of plastic waste. Due to the regulation, it is expected to reduce the generation of plastic waste up to 60-70% so that it can improve environmental quality and have a positive impact on the quality of life and public health as well as Bali tourism. One important point is that being free from plastic will lead Bali into a clean and green island.